2012
DOI: 10.1186/1556-276x-7-626
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic epitaxial ZnO/CdO core/shell heterostructure nanorods

Abstract: Various surface structures and polarities of one-dimensional nanostructures offer additional control in synthesizing heterostructures suitable for optoelectronic and electronic applications. In this work, we report synthesis and characterization of ZnO-CdO nanorod-based heterostructures grown on a-plane sapphire. The heterojunction formed on the sidewall surface of the nanorod shows that wurtzite ZnO {1010} planes are interfaced with rocksalt CdO {100}. This is evidently different from the heterojunction forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Several strategies have been proposed to fabricate highly ordered ZnO NAs, such as nanosphere lithography (NSL) [64][65][66][67][68], electron beam lithography (EBL) [69][70][71][72], optical lithography (OL), and laser interference lithography (LIL) techniques [73][74][75][76][77][78][79][80]. Among these, self-assembled NSL is a simple and economical technique, which employs twodimensional (2D) self-assembled nanometer-sized polystyrene spheres as lithography masks to fabricate patterned arrays [64].…”
Section: Synthetic Methodologies and Properties For Patterned Zno Nasmentioning
confidence: 99%
“…Several strategies have been proposed to fabricate highly ordered ZnO NAs, such as nanosphere lithography (NSL) [64][65][66][67][68], electron beam lithography (EBL) [69][70][71][72], optical lithography (OL), and laser interference lithography (LIL) techniques [73][74][75][76][77][78][79][80]. Among these, self-assembled NSL is a simple and economical technique, which employs twodimensional (2D) self-assembled nanometer-sized polystyrene spheres as lithography masks to fabricate patterned arrays [64].…”
Section: Synthetic Methodologies and Properties For Patterned Zno Nasmentioning
confidence: 99%
“…Advancements have been substantial in the design and understanding of the physical properties of low-dimensional semiconductor heterostructures [ 1 , 2 ]. Low-dimensional semiconductor heterostructures, because of their special band alignment at the interfaces, have potential applications in photoactivated and gas-sensing devices [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…One-dimensional semiconductors with a three-dimensional architecture exhibit a high surface-to-volume ratio and excellent physical and chemical properties [2,6]. Experimental results have revealed that combining two wide band gap semiconductors can yield a novel material featuring improved functions compared with the individual semiconductor material [10][11][12]. In addition to heterostructures, 1D materials with a porous structure or a tube-like morphology have been demonstrated to exhibit superior gas sensing response and sensitivity [13,14].…”
Section: Introductionmentioning
confidence: 99%